Engaging and educating eclipse observers in the Heliophysics Big Year - Reiff, Patricia H.; Caspi, Amir; Sumners, Carolyn T.; Gardner, Charles H.; Kovac, Sarah A. (Frontiers in Astronomy and Space Sciences, 2026)
The “Heliophysics Big Year” was an extended “year” when major solar events engaged the public. NASA and the National Science Foundation (NSF) funded several projects to educate the public on the science of the heliosphere and safe observing practices. In response to this initiative, we worked with other teams to create and disseminate accurate yet engaging information. We expanded our eclipse website (https://space.rice.edu/eclipse/) with activities, citizen science projects, resources, training videos, suggested equipment, and links to other compendia. We directed the Citizen CATE 2024 project, and trained state coordinators and their teams to use the specialized equipment and procedures. We trained teachers at local, regional, national, and international workshops, providing eclipse viewing cards, lenses for making “solar cup projectors,” a pattern for a safe viewing screen, and additional materials. With other teams, we gave presentations to the media at SciLine in San Antonio and hosted public events to demonstrate safe eclipse viewing techniques. The most lasting and impactful product was our planetarium show “Totality,” which was distributed free of license fees. More than 180,000 views of the show and its animations have been documented. We improved our space weather forecasting site (https://mms.rice.edu) and used our email lists (14,000+) to send out real-time warnings about the major solar storm of 10–11 May 2024. In total, we provided nearly two million people with heliophysics information. In summary, the federal/private/business partnerships meant that the events of this “year” were a fun, safe, learning experience for tens of millions of Americans.